ASEAN E-Commerce Legal Framework and Alignment of Lao PDR: A Review - Sengpunya, Phet (University of Jember, 2019)
In the era of digital technology, the internet has become a new channel for meeting and social interaction of people all around the world, and it has also become an essential platform for commercial activities, especially e-commerce. E-commerce has become a significant driving force for the growth of the economy for all regions around the world. For example, ASEAN, ICT, and e-commerce are recognized as an essential segment for regional integration. ASEAN developed its legal framework in order to promote and facilitate the development of ICT and the growth of e-commerce within the region. Unlike the European Union, ASEAN is not a supranational organization, and it cannot legislate for a whole community. Thus its e-commerce legal framework is developed by harmonizing the Member Countries' national laws into the regional legal system. This paper aims to introduce how ASEAN designs its legal framework for regional cooperation, with a focus on e-commerce. The paper presents how Lao PDR, as a member country of ASEAN, fulfills provisions agreed under the e-ASEAN framework to help understand the way ASEAN Member Countries undertake action to align with ASEAN e-commerce legal framework. To this end, this paper also provides an overview of the e-commerce of ASEAN as a whole and Lao PDR. Keywords: ASEAN, Lao PDR, E-Commerce Legal Framework, Regional Legal System.